2004
DOI: 10.1007/s10578-004-1879-0
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Sleep?Wake Patterns of Cosleeping and Solitary-Sleeping Infants

Abstract: This study examined whether 3-15 month-old cosleeping infants displayed differences in time spent in active versus quiet sleep, and in the number/duration of nighttime awakenings when compared with solitary-sleeping infants; and also whether they spent the majority of the night sleeping faceto-face, as previously reported. Nine cosleeping and nine solitary-sleeping infants were matched on age, gender, ethnicity, maternal age, and family SES. Video recordings of nighttime sleep yielded percentage of time in act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 18 publications
6
44
0
Order By: Relevance
“…Experimental research in the sleep lab has shown that babies sleeping close to their nursing mother experience more body and head repositioning during sleep. In addition, they spend more time in active sleep phases during which the gravitational effects on the skull are minimised due to more arousals and a higher muscle tone 17 18. Thus, the social sleep arrangement seems to be able to modify or even nullify the effect of the supine sleep position exposure, making the latter a necessary rather than a sufficient exposure for DP to develop.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental research in the sleep lab has shown that babies sleeping close to their nursing mother experience more body and head repositioning during sleep. In addition, they spend more time in active sleep phases during which the gravitational effects on the skull are minimised due to more arousals and a higher muscle tone 17 18. Thus, the social sleep arrangement seems to be able to modify or even nullify the effect of the supine sleep position exposure, making the latter a necessary rather than a sufficient exposure for DP to develop.…”
Section: Discussionmentioning
confidence: 99%
“…The first is a case-control study of 18 infants. 37 Among 9 roomsharers, 5 were bed-sharers, making conclusions about arousals among those who are room-sharing but not bed-sharing (versus independent sleepers) problematic. The second study, which also included bedsharers in the room-sharing group, states that parental presence in the room at bedtime (eg, holding, rocking, feeding to sleep) explained much of the variance in night wakings and that night-long roomsharing had a "negligible (<1%) independent contribution to the explained variance."…”
Section: Discussionmentioning
confidence: 99%
“…The responsiveness of the mother to infant arousals during bed-sharing might also be protective. Although speculative, this has been suggested also in other studies (Baddock et al 2004;Mao et al 2004).…”
Section: Association Between Bed Sharing and Sudden Infant Death Syndmentioning
confidence: 64%